Risk group assessment of oral precancer attached to X-ray lung-screening examinations - Dombi C, VoÃƒâ€šÃ‚Â¨roÃƒâ€šÃ‚Â¨s-Balog T, CzegleÃƒâ€šÃ‚Â´dy AÃƒâ€šÃ‚Â´ , Hermann P, Vincze N, BaÃƒâ€ (Blackwell Synergy, 2001)
The mortality rate of oral tumours in Hungary, as in some other countries, is increasing. In order to assess risk groups for oral cancer and precancer, oral examinations were carried out as part of the X-ray screenings for lung cancer in the 3rd district of Budapest, Hungary. There were 5034 adults who participated voluntarily in these investigations.